Rethinking Brazilian Government Indigenous Policy for the Botocudo Indians During the 19th Century - Paraiso, Maria Hilda Baqueiro (Revista de Antropologia, 1992)
This article analyses the colonial history of Brazilian states of Bahia, Minas Gerais and Espírito Santo during the 19th century, from an ethnohistorical perspective. Economical interests motiveded the the colonization of this region. The Botocudos Indians inhabited the area and as they didn't accept calmly their land invasion the colonizers used military strategies. This kind of political strategy used to "bring the progess to the area" resulted in the almost total extermination of the Botocudos. The principles on which this kind of contacts with Indian peoples were based are still present in nowa-days indigenous policies in Brazil